Analysing metaphors of katy perry's song lyrics - Rizqi, Nurhana Tri; Mantiri, Ruben Leopoldo (Yayasan Mitra Persada Nusantara, 2024)
This study concentrated on examining metaphor in three Katy Perry songs: Fireworks, Hot n Cold, and Roar. The data in this study were analyzed using qualitative research. According to the findings, there were seven different sorts of metaphors utilized in the three Katy Perry songs. Active metaphor, subjective metaphor, mimetic metaphor, phenomenalistic metaphor, precision metaphor, symbolic metaphor, and approximately metaphor were the seven types of metaphor employed and defined. Overall, based on our analysis, Katy Perry did an excellent job of conveying the idea of the song; she compares a condition of affairs to making it more exciting, and her usage of the word is more varied and broader.